(untitled) (American Journal of Islam and Society, 2011)
Akbar Ahmed’s latest book, Journey into America: The Challenge of Islam, has become one of the first comprehensive ethnographic studies of the Muslim community in America. Ahmed and his team of young researchers offer a keen anthropological analysis of American Muslims that spans over seventy-five cities, one hundred mosques, and two thousand interviews. A modern-day version of Alexis de Tocqueville’s Democracy in America, Journey into America charts the various historical, social, and ideological trajectories that have shaped both American and Muslim identities. As such, the work represents one of the first post-9/11 sociological commentaries that attempt to define the nature of American Muslim identity and the possibilities for its reevaluation. Over the course of nine chapters, Ahmed lays out for a general audience the groundwork for precisely such an endeavor ...